The Genomic Sequence and Comparative Analysis of the Rat Major Histocompatibility Complex - Hurt, Peter; Walter, Lutz; Sudbrak, Ralf; Klages, Sven; Müller, Ines; Shiina, Takashi; Inoko, Hidetoshi; Lehrach, Hans; Günther, Eberhard; Reinhardt, Richard; Himmelbauer, Heinz (Genome Research, 2004)
We have determined the sequence of a 4-Mb interval on rat chromosome 20p12 that encompasses the rat major histocompatibility complex (MHC). This is the first report of a finished sequence for a segment of the rat genome and constitutes one of the largest contiguous sequences thus far for rodent genomes in general. The rat MHC is, next to the human MHC, the second mammalian MHC sequenced to completion. Our analysis has resulted in the identification of at least 220 genes located within the sequenced interval. Although gene content and order are well conserved in the class II and class III gene intervals as well as the framework gene regions, profound rat-specific features were encountered within the class I gene regions, in comparison to human and mouse. Class I region-associated differences were found both at the structural level, the number, and organization of class I genes and gene families, and, in a more global context, in the way that evolution worked to shape the present-day rat MHC.